Enhanced Efficiency in Plant Regeneration of Thai Rice Variety (Pathumthani1) Using Nano-carbon Materials Application - Mekprasart, Wanichaya; Chutipaijit, Sutee (Journal of Advanced Development in Engineering and Science, 2023)
This research was investigated an application of nanomaterials for in vitro callus induction and plant regeneration from seed explants of Thai rice variety (Pathumthani1) using plant tissue culture technique supplemented with nano-carbon. Callus induction was initiated and established from rice seeds. Explants were cultured on NB medium supplemented with various concentrations of 2,4-D (1-5 mg L-1). Green spots and plant regenerations were induced using NB medium supplemented with various concentrations of BA (1-5 mg L-1). Optimum concentration of 2,4-D (3 mg L-1) and BA (3 mg L-1) showed highly induced the callus inductions and plant regenerations, respectively. Moreover, NB medium supplemented with 3 mg L-1 of 2,4-D for callus induction, 3 mg L-1 of BA for plant regeneration and various concentrations of nano-carbon (0-80 mg L-1) were successfully induced the plant regeneration which percentage of green spots were 85.56-94.44%, plant regenerations were 37.78-57.78% and the ratio of seedlings per callus were 2.06-2.31. The highest percentage of green spots (94.44%), plant regenerations (57.78%) and the ratio of seedlings per callus (2.31) was obtained from NB medium supplemented with 3 mg L-1 of 2,4-D for callus induction, 3 mg L-1 of BA and 40 mg L-1 of nano-carbon for plant regeneration. The results indicated that nano-carbon materials could be used to potential micropropagation for Thai rice variety (Pathumthani1) and application in other plant species.